What is my calling? : a biblical and theological exploration of Christian identity - Klein, William W. (William Wade); Steiner, Daniel J., 1980- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2022)
"Dismantles confused notions of what it means to have a "calling" and offers a clear biblically and theologically informed view of what a Christian calling truly is"--
Includes bibliographical references (pages 177-184) and indexes.
Keywords: Vocation -- Christianity; Identity (Psychology) -- Religious aspects -- Christianity